남북경제협력에 따른 개발이익 경매와 DMZ 보전기금 확보 - 박호정; Hojeong Park; 김준순; Joonsoon Kim; 김현희; Hyunhee Kim (자원·환경경제연구, 2019)
DMZ는 반세기 이상 인위적 활동이 배제되어 우수한 생태계를 보유하고 있다. 통일 이후에도 DMZ의 생태계는 보전되어야 하며 이를 위해서는 남북한 통일 이후가 아니라 사전에 그 보전방안이 마련되어야 한다. DMZ 생태자원 보전에는 생태자원 관리 비용 뿐만 아니라 복구비용 및 연구예산까지 수반되어야 하므로 상당한 규모의 예산이 필요하다. 이에 본 논문은 실물옵션과 경매이론을 연계하여 경제적 인센티브 메커니즘을 이용한 DMZ 보전기금 확보 방안을 연구하고자 한다. 다수의 사업자들은 경매를 통해 북한지역 개발사업권을 획득하려고 하고, 매몰비용에 대한 사적 정보를 가지고 있으며, 사업수익의 일부를 보전기금으로 지불한다고할 때, 먼저, 경매 참가자의 최적 투자시기를 결정하는 실물옵션 모형을 분석하고, 다음으로 베이즈 내쉬균형을 이용해 경매 참가자가 사적 정보에 대해 진실을 보고할 경매를 설계한다. The Korean Demilitarized Zone (DMZ) has the great ecosystem as all the artificial activities in DMZ have been prohibited over half a century. The ecosystem should be conserved even after the reunification of Korea and hence the conservation plan should be established not after the reunification but before it. It requires a considerable budget to conserve DMZ, considering management of ecology resource, recovery, and research. The objective of this paper is to analyze a fund-raising measure for DMZ conservation, using economic incentives mechanism when multiple developers participate in the auction to get the right to develop North Korean regions, have private information about their sunk costs and pay a part of their profits for the fund. First, we analyze the real option model to decide the optimal investment time. Second, we construct the auction for bidders not to misrepresent their private information, based on Bayesian Nash equilibrium.